Changes in EMG and movement velocity during a set to failure against different loads in the bench press exercise. (9th August 2021) - Tsoukos, Athanasios; Brown, Lee E.; Terzis, Gerasimos; Wilk, Michal; Zajac, Adam; Bogdanis, Gregory C.
Abstract : This study examined changes in movement velocity and surface electromyographic (sEMG) activity of the pectoralis major (PM) and triceps brachii (TB) muscles during the bench press exercise to failure against different loads. Fourteen men performed a set to failure with maximum intended velocity, against low (40%‐1 repetition maximum‐RM), moderate (60%‐1RM), and heavy loads (80%‐1RM). Number of repetitions, volume load, mean and peak velocity, and total time increased with decreasing load (40% > 60% > 80%, p < 0.01). sEMG comparisons between different loads were performed by matching time under tension at the initial, middle, and last part of the set. sEMG was higher in the middle and last repetitions, compared with the initial, for all loads in both muscles ( p < 0.001). sEMG activity of both muscles was higher in the 60% and 80%‐1RM conditions compared with the 40%1‐RM ( p < 0.007). Also, sEMG of both muscles was similar for the 60%‐1RM and 80%‐1RM loads at the initial, middle, and last repetitions, with the exception of the last repetitions for the TB muscle. In contrast, sEMG integrated activity was higher for the 40% 1‐RM and 60% 1‐RM ( p < 0.01) compared with the 80% 1‐RM load. Mean velocity loss at exhaustion and drop in sEMG median frequency were greater in the 40% and 60%‐1RM compared with the 80%‐1RM condition ( p < 0.05). It was concluded that performing a set to exhaustion with maximum intended velocity using a load of 60% 1‐RM combines the characteristics of the high average sEMG activity of heavier loads, and the high total integrated sEMG observed at lighter loads.